Genetic diversity and relationships among isolates of Rhizobium leguminosarum biovar phaseoli. - Pinero, D (1988)
Fifty-one isolates of Rhizobium leguminosarum biovar phaseoli from various geographic and ecological sources, largely in Mexico, were characterized by the electrophoretic mobilities of 15 metabolic enzymes, and 46 distinctive multilocus genotypes (electrophoretic types [ETs]) were distinguished on the basis of allele profiles at the enzyme loci. Mean genetic diversity per enzyme locus among the 46 ETs was 0.691, the highest value yet recorded for any species of bacterium. The occurrence of strong nonrandom associations of alleles over loci suggested a basically clonal population structure, reflecting infrequent recombination of chromosomal genes. Multilocus genotypic diversity was unusually high, with the most strongly differentiated pairs of ETs having distinctive alleles at all 15 loci and major clusters of ETs diverging at genetic distances as large as 0.89. This great diversity in the chromosomal genome raises the possibility that R. leguminosarum biovar phaseoli is a polyphyletic assemblage of strains. As other workers have suggested, the inclusion of all strains capable of nodulating beans in a single biovar or species is genetically unrealistic and taxonomically misleading. A biologically meaningful classification of Rhizobium spp. should be based on assessment of variation in the chromosomal genome rather than on phenotypic characters, especially those mediated for the most part or wholly by plasmid-borne genes, such as host relationships.